Strengths and weaknesses of the German translation of the Inflexible Eating Questionnaire and of eating disorder assessment in general - Schultz, Anna; Maurer, Linda; Alexandrowicz, Rainer W. (Frontiers in Psychology, 2022)
Objective The present article introduces the German translation of the Inflexible Eating Questionnaire (IEQ-G), performs a psychometric evaluation, and explores the relationship of Inflexible Eating to the subscales of the Eating Disorder Examination-Questionnaire (EDE-Q) and Obsessive-Compulsive (OC) symptoms. Methods The cross-sectional study was carried out in the German-speaking area. A paper and pencil survey was completed by 612 females and 442 males of the general population. Results SEM analyses showed that the IEQ-G allows for calculating a total score and invariance tests were mostly promising. As a side result, the original 4-factorial structure of the EDE-Q could not be replicated, but a 3 dimensional solution proved convincing. From a psychometric point of view, the IEQ-G outperformed the EDE-Q. On a latent level, Inflexible Eating was remarkably strong related to OC-symptoms and the EDE-Q subscales. Discussion The detail analyses revealed that Eating Disorder assessment in general lacks subgroup-specific aspects, for instance, regarding gender or dietary preferences, important for early diagnosis and screening of ED. The IEQ-G proved applicable in a German speaking adult population and recommends itself for cross-cultural studies.